Influence of food and lifestyle on the risk of developing inflammatory bowel disease. Issue 6 (3rd June 2016) - Niewiadomski, O.; Studd, C.; Wilson, J.; Williams, J.; Hair, C.; Knight, R.; Prewett, E.; Dabkowski, P.; Alexander, S.; Allen, B.; Dowling, D.; Connell, W.; et al.
Abstract : Background: The Barwon area in Australia has one of the highest incidence rates of inflammatory bowel disease (IBD) and therefore is an ideal location to study the impact of environmental exposures on the disease's development. Aim: To study these exposures prior to the development of IBD in a population‐based cohort. Method: One hundred and thirty‐two incident cases (81 Crohn disease (CD) and 51 ulcerative colitis (UC)) from an IBD registry and 104 controls replied to the International Organization of Inflammatory Bowel Diseases environmental questionnaire. This included 87 questions about pre‐illness exposures that included childhood illnesses, vaccinations, breastfeeding, house amenities, pets and swimming, diet and smoking. Results: The factors associated with CD included smoking (odds ratio (OR): 1.42, confidence interval (CI): 1–2.02, P  = 0.029); childhood events, including tonsillectomy (OR: 1.74, CI: 1.15–2.6, P  = 0.003) and chicken pox infection (OR: 3.89, CI: 1.61–9.4, P  = 0.005) and pre‐diagnosis intake of frequent fast food (OR: 2.26, CI: 1.76–4.33, P  = 0.003). In UC, the risk factors included smoking (OR: 1.39, CI: 1.1–1.92, P  = 0.026) and pre‐diagnosis intake of frequent fast food (OR: 2.91, CI: 1.54–5.58, P  < 0.001), and high caffeine intake was protective (OR: 0.51, 95% CI: 0.3–0.87, P  = 0.002). Other protective exposures for UC included high fruit intake (OR: 0.59, CI: 0.4–0.88, P  = 0.003) and having pets as a child (OR: 0.36, CI: 0.2–0.79, P  = 0.001). Conclusion: This first Australian population‐based study of environmental risk factors confirms that smoking, childhood immunological events and dietary factors play a role in IBD development; while high caffeine intake and pet ownership offer a protective effect.